2021
DOI: 10.7759/cureus.17435
|View full text |Cite
|
Sign up to set email alerts
|

Sudden Sensorineural Hearing Loss Following the Second Dose of COVID-19 Vaccine

Abstract: Sudden sensorineural hearing loss (SSHL) is a common otolaryngology emergency that significantly affects the patient’s quality of life. Although in most cases its etiology remains unknown (idiopathic SSHL), viral infections and vascular compromise constitute the most widely accepted etiopathogenic mechanisms. Specifically, occlusion of the internal auditory artery has been reported in cases of sudden deafness. Thrombotic events following the Oxford-AstraZeneca COVID-19 vaccine are rare. There have been reports… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 8 publications
1
41
0
3
Order By: Relevance
“…Indeed, it is worth citing a research letter from Formeister from Johns Hopkins University School of Medicine, Baltimore, which reported that the incidence of SSNHL occurring after COVID-19 vaccination does not exceed that of the general population, and may be lower ( 18 ). Although there is no direct evidence of the association between vaccination and SSNHL, some cases of SSNHL after COVID-19 vaccination have been recently reported ( 19 , 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it is worth citing a research letter from Formeister from Johns Hopkins University School of Medicine, Baltimore, which reported that the incidence of SSNHL occurring after COVID-19 vaccination does not exceed that of the general population, and may be lower ( 18 ). Although there is no direct evidence of the association between vaccination and SSNHL, some cases of SSNHL after COVID-19 vaccination have been recently reported ( 19 , 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many authors have considered a possible link between COVID-19 infection and SSHL [2,[6][7][8][9][10]; however, as far as the author knows this is the first case series considering the possible association between a COVID-19 vaccine and inner ear damage, which could indeed have pathophysiology similar to that of the cases of SSHN secondary to COVID-19 infection. We display the audiometries of cases 1 and 5 since we believe them to be the most representative of the situation described by Tseng et al [12] (case 1) and the one described by Tsetsos et al [11] (case 5). Even if two cases presented here did not clearly show the traditional full criteria for SSHL, the presentation was very similar to a traditional SSHL and both were treated as such by using steroids similar to what was described by Tseng et al [12], with most cases having the resolution of the symptoms around the day 3 of management.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous reports have mentioned the possible link between COVID-19 infection and inner ear damage [2,[6][7][8][9][10]; however to the authors´ very best knowledge this is the first case series considering the possible association between AZCV (or any COVID-19 vaccine) and inner ear damage, and so far only two previous isolated single case reports of auditory symptoms related to the AZCV have been described, including one report of SSHL itself [11], and one report of tinnitus presumably associated to cochleopathy secondary to the vaccine [12]. To our best knowledge, this is the first report of a patient with vestibular symptoms related to the AZCV.…”
Section: Introductionmentioning
confidence: 88%
“…Tsetsos et al [ 22 ] in August 2021, reported a SSNHL, without tinnitus and vertigo, two days after the second dose of the AstraZeneca COVID-19 vaccine. The patient was a 61-year-old female with a history of hypertension, dyslipidemia, and thyroiditis, under pharmacological treatment long-term.…”
Section: Resultsmentioning
confidence: 99%
“…Among the selected papers, seven were related to SSNHL following COVID-19 immunization, mainly with associated tinnitus [ 21 , 22 , 23 , 24 , 25 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%